2020
DOI: 10.1177/1475921720911153
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ultrasonic evaluation of disorderedly clustered pitting damage using an in situ sensor network

Abstract: Pervasive but insidious, pitting damage—from pitting corrosion in maritime structures through electrical pitting in bearings to debris cloud–induced pitting craters in spacecraft—is a typical modality of material degradation and lesion in engineering assets in harsh service environment. Pitting damage may feature hundreds of clustered, localized craters, cracks, and diverse microscopic defects (e.g. dislocation, micro-voids, and cracks) disorderedly scattered over a wide area. Targeting accurate, holistic eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…A Rayleigh wave is guided by a free surface of a waveguide and constrains its major energy to the waveguide surface. With the energy dominance near to the waveguide surface, Rayleigh-Lamb waves have been employed to locate [23,24], orientate [25] and evaluate [26][27][28][29] surface or sub-surface flaws. Amongst demonstrated paradigms, the second harmonic generation is one of the wave features that has been exploited extensively.…”
Section: Introductionmentioning
confidence: 99%
“…A Rayleigh wave is guided by a free surface of a waveguide and constrains its major energy to the waveguide surface. With the energy dominance near to the waveguide surface, Rayleigh-Lamb waves have been employed to locate [23,24], orientate [25] and evaluate [26][27][28][29] surface or sub-surface flaws. Amongst demonstrated paradigms, the second harmonic generation is one of the wave features that has been exploited extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed that a method using scanning laser Doppler vibrometer (SLDV) can detect a cluster of pits which are arranged in 3 × 3 × 3 array and have the diameter of 2 mm and the interval of 2 mm in aluminum plate, but most pits except the one at the center of cluster can be identified [ 13 , 14 ]. Recently, Cao et al proposed the NI, which can link the degree of nonlinearity to the size of pitting damage, and both the PZTs network and RAPID algorithm are used to visualize pitting damage, but only an approximate range of pitting corrosion can be located [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The higher order harmonics can be generated upon nonlinear interaction between a probing wave and microstructural degradation in a waveguide that is associated with dislocation, phase change, void nucleation and plastic deformation. There is a rich body of literature, in numerical or experimental natures [9][10][11][12], to reveal that the higher order harmonics of GUWs are more sensitive to contact-type defect (e.g., fatigue cracks or delamination under the modulation of external loads), yet less affected by ambient variations (e.g., environmental noise or temperature fluctuation) than the linear features of GUWs including the coefficients of wave transmission/reflection, distortion of waveform, and delay in wave arrival time [13][14][15][16][17][18][19][20][21]. Amongst the higher order harmonics, the second order harmonics are extensively explored, owing to their relatively stronger magnitudes and easier acquisition, compared with harmonics of higher orders.…”
Section: Introductionmentioning
confidence: 99%